2018
DOI: 10.1016/j.jvs.2017.12.078
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychiatric comorbidities on patient-reported surgical outcomes in adults treated for the median arcuate ligament syndrome

Abstract: Surgery improves patient-reported QOL in adults treated for MALS. Psychiatric diagnoses are common in adults with MALS and predict worse patient-reported QOL outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Therefore, this study suggests that operative management of MALS is safe with low morbidity and mortality; however, the risks of unsuccessful symptom resolution or symptom recurrence need to be discussed with the patient. MALS is associated with substantial psychosocial impact, 13,19 with the afflicted often rendered chronically impaired owing to pain and treated medically with limited success. Surgical intervention has thus been offered as a last resort, although to date the long-term ability to provide symptomatic relief with operative intervention has been unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this study suggests that operative management of MALS is safe with low morbidity and mortality; however, the risks of unsuccessful symptom resolution or symptom recurrence need to be discussed with the patient. MALS is associated with substantial psychosocial impact, 13,19 with the afflicted often rendered chronically impaired owing to pain and treated medically with limited success. Surgical intervention has thus been offered as a last resort, although to date the long-term ability to provide symptomatic relief with operative intervention has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, there are few long-term data on symptom recurrence and health-related quality of life (HRQOL) after operative management of MALS in the adult population. [11][12][13] The aim of this study was to investigate long-term patient-reported outcomes after the surgical treatment of MALS.…”
mentioning
confidence: 99%
“…1,2 The syndrome is characterized by chronic severe postprandial abdominal pain, nausea, vomiting, and weight loss that may range from mild to severe and has led to much controversy regarding its clinical existence and optimal management. [3][4][5][6] The debate is perpetuated by the finding of extrinsic celiac compression in both autopsy studies and celiac angiography in asymptomatic patients. 2 Ultimately, mixed enthusiasm for surgical treatment in patients with this condition continues to exist, especially in those confounded by other comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…2 Ultimately, mixed enthusiasm for surgical treatment in patients with this condition continues to exist, especially in those confounded by other comorbid conditions. [4][5][6] Of note, SMA syndrome is a somewhat common diagnosis in patients with AN who develop postprandial abdominal pain due to weight loss, atrophy of mesenteric fat, and subsequent duodenal compression.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature search showed 2 studies on quality of life after CMI revascularisation. The first, by Skelly et al [24], describes psychiatric comorbidities in MALS patients undergoing surgery, trying to determine whether these comorbidities are predictive of patient-reported quality of life outcomes. They concluded that patient-reported quality of life significantly improved after surgical therapy for MALS patients but that a pre-existing psychiatric disorder has a poorer outcome in some domains.…”
Section: Discussionmentioning
confidence: 99%